Influence and mechanism of different molecular weight organic molecules in natural water on ultrafiltration membrane fouling reversibility. Issue 86 (2nd September 2016) - Sun, Weiguang; Nan, Jun; Xing, Jia; Tian, Jiayu
Abstract : To investigate the influence of different molecular weight distribution to UF membrane fouling, NOM in natural water was fractionated into five components based on their size and their potential to develop the membrane fouling was conducted. Abstract : To investigate the influence of different molecular weight distributions on UF membrane fouling, NOM in natural water was fractionated into five components: <5 kDa, 5–10 kDa, 10–50 kDa, 50–100 kDa, and 100 kDa-0.45 μm, based on their size and potential to develop irreversible membrane fouling (IF). Reversible membrane fouling (RF) was conducted by unstirred cell test. The size fractionation combined with PARAFAC of three-dimensional fluorescence excitation-emission matrix (EEM) of fractions was performed to identify the substances responsible for IF and RF. Moreover, a mass balance analysis coupled with a correlation analysis was performed to acquire information on the organic matter fouling behavior. Based on the fouling effect, a scanning electron microscope (SEM) was used for mechanism analysis. In the five fractions, the 100 kDa-0.45 μm fraction, which only accounted for 7.2% DOC and in which protein-like substances recognized by EEM-PARAFAC existed, contributed the most to the membrane flux decline caused by both IF and RF. The <5 kDa fraction, which accounted for 70% DOC and mainly contained humic-like substances and protein-like substances, caused little flux decline, but the contribution was irreversible. Mechanism analysis made it clear that the small molecular substances (<5 kDa, 5–10 kDa) caused irreversible flux decline of the membrane through pore blocking, and large organic molecules (50–100 kDa, 100 kDa-0.45 μm) contributed to irreversible and reversible membrane fouling through pore blocking and cake layer forming. It is important to consider the contribution of <5 kDa and 100 kDa-0.45 μm in the choice of pretreatment technologies to control membrane fouling.